(untitled) (Research, Society and Development, 2020)
The present research aimed to evaluate in silico the pharmacodynamics, pharmacokinetics and toxicity of syringic and ursolic acids isolated from Actinidia delicious and to analyze the mechanism that underlies its performance in cholesterol reduction comparing them with the drug simvastatin. The PreADME online server was used to evaluate the pharmacokinetic and toxicological profile through the molecular structure-activity and the AutodockVina software to study the pharmacodynamics and pharmacological potential of molecular interactions. The ADME data obtained for the syringic and ursolic acids were similar to those for simvastatin, in the analysis of the molecular docking it was evidenced that the results were approximate between the tested molecules, however the ursolic acid overlapped with greater interaction stability with the biological target when compared to simvastatin. It was possible to observe from the results that the evaluated compounds are qualified for subsequent in vitro and in vivo tests for a more in-depth study of their anti-hyperlipemic action.